Uneven Outcomes of Urban Revitalization: Socioeconomic Impacts of the Masbagik Intersection Transformation into an MSME and Public-Space Hub in East Lombok, Indonesia - Luqyana Salsabila Atikha; Emi Salmah (Future Techno-Science, 2026)
This study examines the socioeconomic impacts of the revitalization of Masbagik Intersection in East Lombok, Indonesia, where part of a strategic roadside area was transformed into an MSME hub and integrated public space. A qualitative case-study design was employed using observation, documentation, and semi-structured interviews with regional-government representatives, new MSME vendors, relocated shop and street vendors, visitors, and local residents. The data were analyzed thematically and triangulated across stakeholder groups. The findings show that revitalization generated new livelihood opportunities, improved the visibility of small businesses, increased daily sales among new MSME vendors by 33.3% to 200.0%, and created a public space for recreation, food consumption, and social interaction. However, the benefits were unevenly distributed. Relocated and older street vendors reported income decreases of 12.0% to 37.5%, while local residents identified traffic congestion and parking pressure as emerging social costs. Stakeholder expectations focused on better facilities, wider and fairer stall allocation, improved cleanliness, parking management, and more inclusive economic benefits. The study demonstrates that revitalization should not be evaluated only through physical improvement or visitor crowds. It must also be assessed through distributive outcomes, continuity of livelihoods, and the capacity of local governance to manage post-project externalities. The case contributes to debates on small-town urban regeneration by showing how an MSME-oriented public-space intervention can simultaneously activate local economies and reproduce vulnerabilities among pre-existing informal actors.